Electrochemical Characterization of Electrodeposited Ni–Cu Foams and Their Application as Electrodes for Supercapacitors - Abdelfatah, Aliaa; Reda, Yasser; Abdel-Karim, Randa; El-Raghy, S. M.; Zohdy, Khaled M. (Frontiers in Mechanical Engineering, 2020)
Nanoporous nickel–copper metallic foams were electordeposited using hydrogen templating (DHBT) technique. The effect of deposition parameters (applied current density and deposition time) on surface morphology of the obtained layers was studied with the aid of SEM. The Ni–Cu electrodeposited layers were characterized by a porous dendritic structure. According to EDX analysis, increasing both the deposition time and applied current density leads to an increase of the Ni content in the nano-foams. These foams were tested as electrodes for supercapacitors in 1 M KOH solutions. From potentiodynamic polarization test, the corrosion rate was accelerated with increasing the deposition time up to 150 s as well as the deposition current density up to 1.8 A/cm2. The electrochemical behavior of the material was studied by cyclic voltammetry aiming at its application as positive electrodes for supercapacitors, using 1 M KOH solution. From cyclic voltammetry, toth the increase of applied current density and the deposition time lead to an increase of the current density and total charge measured by cyclic voltammetry, having a beneficial effect on the electrochemical activity of the Ni-Cu films. The highest forward current peak was obtained for nickel–copper foams deposited at 2 Acm-2 for 150 s. From EIS test, the polarization resistance (Rp) decreased with increasing the current density as well as electrodeposition time. The lowest polarization resistance was recorded for porous Ni-Cu layers electrodeposited at 2 A/cm2 for 150 sec, indicating high electrochemical activity of this layers (35.02%Cu) as electrodes for supercapacitors.